Application of Environmental, Social, and Governance (ESG) Method in Financial Management - Fadli, Zahri (Universitas Muhammadiyah Sumatera Utara, 2024)
This study investigates how the Environmental, Social, and Governance (ESG) approach can be used in financial management. Investors can avoid companies that have regulatory, reputational and social risks by considering environmental, social and governance considerations. Empirical evidence shows that companies with strong ESG policies typically demonstrate efficacy, ingenuity, and better brand image—all of which contribute to improved financial results and investor appeal. In this research, descriptive analysis is combined with literature study methodology. Transparent ESG reporting enables companies to increase capital availability, meet changing regulatory requirements, foster investor confidence, and lower reputational risk. To achieve this, effective ESG reporting must be implemented through integration with annual reports, acceptance of reporting standards, stakeholder engagement and independent verification.